Gender‐Intrusive Questioning: A Survey of Expert Witnesses. (March 2014) - Daftary‐Kapur, Tarika; O'Connor, Maureen; Mechanic, Mindy; Brodsky, Stanley L.
<x xml:space="preserve">Abstract</x> This paper reports the results of a survey of male and female psychologists with expert witness experience. The survey explored the roles of both expert witness gender and valence of the testimony to provide preliminary empirical data on whether gender in combination with the valence of testimony leads to perceived bias targeted towards female experts. The presence of such bias might diminish the credibility of the expert and subsequently the proffered testimony and, thus, undermine the legal system as effective fact‐finder by leading to decision‐making based on extra‐legal factors. Copyright © 2014 John Wiley & Sons, Ltd.